Hepatic Steatosis and Ectopic Fat Are Associated With Differences in Subcutaneous Adipose Tissue Gene Expression in People With HIV. Issue 7 (27th February 2021) - Gabriel, Curtis L.; Ye, Fei; Fan, Run; Nair, Sangeeta; Terry, James G.; Carr, John Jeffrey; Silver, Heidi; Baker, Paxton; Hannah, LaToya; Wanjalla, Celestine; Mashayekhi, Mona; Bailin, Sam; et al.
Abstract : Persons with human immunodeficiency virus (PWH) have subcutaneous adipose tissue (SAT) dysfunction related to antiretroviral therapy and direct viral effects, which may contribute to a higher risk of nonalcoholic fatty liver disease compared with human immunodeficiency virus–negative individuals. We assessed relationships between SAT expression of major adipocyte regulatory and lipid storage genes with hepatic and other ectopic lipid deposits in PWH. We enrolled 97 PWH on long‐term antiretroviral therapy with suppressed plasma viremia and performed computed tomography measurements of liver attenuation, a measure of hepatic steatosis, skeletal muscle (SM) attenuation, and the volume of abdominal subcutaneous, visceral, and pericardial adipose tissue. Whole SAT gene expression was measured using the Nanostring platform, and relationships with computed tomography imaging and fasting lipids were assessed using multivariable linear regression and network mapping. The cohort had a mean age of 47 years, body mass index of 33.4 kg/m 2, and CD4 count of 492 cells/mm 3 . Lower liver attenuation, a marker of greater steatosis, was associated with differences in SAT gene expression, including lower lipoprotein lipase and acyl‐CoA dehydrogenase, and higher phospholipid transfer protein. Lower liver attenuation clustered with lower visceral adipose tissue (VAT) attenuation and greater VAT volume, pericardial fat volume and triglycerides, but no relationship was observed between liver attenuation and SAT volume, SM attenuation, or low‐density lipoprotein. Conclusion: Liver attenuation was associated with altered SAT expression of genes regulating lipid metabolism and storage, suggesting that SAT dysfunction may contribute to nonalcoholic fatty liver disease in PWH. SAT gene‐expression relationships were similar for VAT volume and attenuation, but not SM, indicating that ectopic lipid deposition may involve multiple pathways. Abstract : image